Beta glucan induced immune priming protects against nervous necrosis virus infection in sevenband grouper. Issue 121 (February 2022) - Krishnan, Rahul; Jang, Yo-Seb; Oh, Myung-Joo
Abstract: In the present study, we studied the effect of β-glucan on the activation of antiviral immune responses against nervous necrosis virus (NNV) taking into consideration the role of innate immune training. Sevenband grouper primary macrophages showed an attenuated proinflammatory response and elevated antiviral response to NNV infection. In vitro, priming of β-glucan enhanced macrophage viability against NNV infection which is associated with the activation of sustained inflammatory cytokines gene expression. Observations were clear to understand that NLR Family CARD Domain Containing 3 (NLRC3) and caspase-1 activation and subsequent IL-1β production were reduced in β-glucan–primed macrophages. Subsequent markers for training including Lactate and abundance of HIF-1α were elevated in the cells following training. However, the lactate dehydrogenase (LDH) concentrations remained stable among the β-glucan stimulated infected and uninfected groups suggesting similar macrophage health in both groups. In vivo, the NNV-infected fish primed with β-glucan had a higher survival rate (60%) than the control NNV-infected group (40%). Our findings demonstrate that β-glucan induced protective responses against NNV infection and studies are underway to harness its potential applicability for prime and boost vaccination strategies. Highlights: Macrophages showed an attenuated proinflammatory response and elevated antiviral response to NNV infection. NLRC3 and caspase-1 activation and subsequent IL-1β production were reduced in β-glucan–primed macrophages. Lactate and abundance of HIF-1α were elevated in the cells following glucan stimulation indicated immune training. NNV-infected fish primed with β-glucan had a higher RPS (60%).